Axiology on the Integration of Knowledge, Islam and Science - Mas’ud Zein (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
The integration of Islamic and science was done through integration-interconnected, referring to ontological, epistemological dan axiological perspectives. This paper will focus on the integration of Islam and science from axiological perspective. Â In the view of axiology, science is seen as neutral and value-free; the value of science is given by its users. This condition motivates Muslim scholars to reintegrate science and religion. The first attempt made is my giving ideas on the Islamization of science. The attempt to Islamize the science in the Islamic world is dilemmatic, whether to wrap western science with the label of Islam or Islamic, or transforming religious norms based the Qurâ€™an and the Hadith to fit empirical data. Both strategies are difficult if the effort is not based on the critic of epistemology.